Evaluation of Quinolone Resistance in Escherichia coli Isolates Recovered from Urine and Feces of Patients with Acute or Recurrent Urinary Tract Infection - Hossein Norouzian; Nader Shahrokhi; Shahram Sabeti; Saeid Bouzari; Mohammad Pooya (Pasteur Institute of Iran, 2019)
Introduction: Antibiotic resistance, especially in Gram-negative uropathogens such as Escherichia coli, is the main barrier to treat urinary tract infection (UTI). In recent years, the dramatically increased resistance of E. coli to quinolones, a group of widely used antibiotics, has become a significant concern. Methods: In this descriptive cross-sectional study, we collected 261 E. coli isolates from the urine and stool samples of patients, referred to or hospitalized at Loghman hospital in Tehran, Iran, with either acute or recurrent UTI. The susceptibility testing for quinolones was performed by the disk diffusion method according to the recent protocols. Results: The frequency of resistant E. coli isolates was higher against nalidixic acid than ciprofloxacin and norfloxacin (67.8% vs. 48.7% and 44.1% respectively). When comparing acute and recurrent phases of UTI, in the urine samples, no significant difference was seen in the frequency of resistant isolates against nalidixic acid and norfloxacin, while this frequency against ciprofloxacin was significantly higher in recurrent UTI (68% vs. 48.2%). However, in the stool samples, the frequency of resistant isolates against nalidixic acid was higher in recurrent UTI (77.1% vs. 55.7%), while no significant difference was seen against ciprofloxacin and norfloxacin in these phases. Conclusion: Regarding the antibiotic type and frequency of the administration, the resistance pattern of E. coli to quinolones seems to differ in acute and recurrent phases of UTI.